Aprendizaje basado en retos en las operaciones básicas matemáticas del 7mo grado de la Escuela “Héctor Nelson García Solano”, Tacamoros - Sozoranga 2023 - Albán Cabrera, Juan Carlos (2023)
This research aims to evaluate, develop, and explain the Challenge-Based Learning (CBL) approach as a pedagogical proposal to enhance basic mathematical operation skills among seventh-grade students at Héctor Nelson García Solano Basic Education School. To theoretically underpin CBL, an exhaustive literature review on its foundations and purposes was conducted. Authors such as Darling-Hammond and Jiménez were pivotal in formulating challenges based on real problems as a starting point for learning, promoting the development of cognitive skills like critical thinking, problem-solving, and creativity, as well as social and emotional skills such as effective communication, teamwork, and perseverance. In this mixed-methods study, a non-random sampling method was employed to select participants. The results and conclusions identified a significant lack of knowledge in the four basic mathematical operations among the students; however, a notable improvement was observed in students with the implementation of the pedagogical proposal based on CBL. The findings and conclusions of this research are used as a reference point and a foundation for future research in this field. Keywords: teaching - learning, basic operations, mathematics, learning Based on Challenges (ABR)